Some Considerations for Further Development of Music Therapy in Korea - Chong, Hyun Ju (Voices: A World Forum for Music Therapy, 2005)
The development of music therapy in Korea has been rapid as any other nation in Asia. Music therapy curriculum was first established in 1997 at the graduate level, and the educational and clinical trainings have become strong. Among many reasons, the main one is that the trained music therapist from U.S., Europe, and Australia have returned, contributed their expertise and incorporated insightful ideas to the music therapy program.Music therapy is an attractive field, with lots of spot light and vision. However, music therapists should work out some of the intra-discipline issues on the professional and educational/training, in order to facilitate further development of music therapy. Among many issues, I would like to articulate a few.